ARch4maps: A mobile augmented reality tool to enrich paper maps - Gaspar, F. (2016)
This paper describes an augmented reality app running on a Windows tablet that recognizes image features on a city paper map and overlays, in real-time, digital content related to the relevant buildings of the city. The system register in 3D the location of those buildings in the map, enriching the user experience with several multimedia information per building: image, text and 3D models which can be explored in detail in an included BIM viewer. Displayed buildings can be queried and filtered by associated meta-data such as decade, author, conservation, etc. The main target users of this system are tourists or users interested in architecture or history. Our usability evaluation study conducted with several users shown that our app increase the scope of applicability of a paper map.